The Investigation of The Imperative Sentences In The Oral Language of Geliting Community - Fadhillah Makuasong, Novita; ., Novi (Udayana Journal of Social Sciences and Humanities; Vol 5 No 1 (2021): UJoSSH, February 2021, 2021)
Every language has its way of switching a positive sentence to a question form. However, the way each language does this is based on a grammar set. Besides this, in every language of the world, there are polar questions and there are content questions. In polar questions, a yes/no answer is adequate as a response; while content questions require sentential structure as an answer. In this study, the writer describes the polar questions formation and content questions formation in Geliting dialect, a language situated within Sikka speech form, spoken in Maumere, Flores island Southeast island. This study shows that Geliting dialect operates a kind of derivation in its interrogative formation.